The structure of the Heath Steele Mines region, Bathurst Camp, New Brunswick - de Roo, J,; Moreton, C.; Williams, P.; Staal, C. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1990)
This paper deals with the structure of the region surrounding Heath Steele Mines, which is situated in the southern part of the Ordovician volcanic-sedimentary complex of the Bathurst Camp, New Brunswick. In this area, five generations of deformation structures are recognized on the basis of orientation, tectonic style, and systematic overprinting relationships. The earliest recognizable deformation (D,) is characterized by tight to isoclinal F, folds of a compositional layering (S,). A cleavage (S,) parallel to the axial plane of these folds was locally rotated into a transposition foliation (S2) during the D2 deformation. Where gently dipping, S2 was cast into domes and basins in two events (D, and D,) of upright folding with axial plane cleavages S¥ and S}. Where steeply dipping, S2 was subjected to recumbent folding (Dk) prior to the fifth deformation (D,). Overprinting relationships between the D( and Dk events are ambiguous, so their correlation with the third and fourth deformations remains open to interpretation. The macroscopic structure in the Heath Steele Mines area is dominated by an open fold (the North Little River Lake Fold) of a belt of metasedimentary rocks and augen schists. This belt is host to the Heath Steele sulphide orebodies and is also an F, fold zone. The age of the macroscopic fold is not well constrained, but the asymmetry of second-order F2 folds reverses across its hinge, and its southwestern limb is attenuated in a zone of high D2 strain, suggesting that it is an F2 fold. The zone of high D2 strain separates the folded belt of metasedimentary rocks and augen schists from a pod of massive porphyry and granitoid rocks.